POLA PRODUKSI DAN KONSUMSI YANG BERTANGGUNGJAWAB PADA KOMODITAS KOPI DAN COKLAT - Sulistyo Sulistyo; Yuni Mariani Manik (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Coffee is a very important agricultural commodity, produced in around 80 countries tropics, with an estimated 125 million people depending on it for their livelihoods in Latin America, Africa and Asia, with an annual production of around nine million tons of mung beans. Consisting of at least 125 species, the coffee genus (Rubiaceae, Ixoroideae, Coffeeae) is distributed in Africa, Madagascar, the Comoros Islands, the Mascarene Islands (La Réunion and Mauritius), tropical Asia, and Australia. Two species are economically important for the production of beverage coffee. arabica. (Arabica coffee) and. canephora. Froehner (robusta coffee). Higher quality of the drink is associated with arabica. Arabica coffee is a self-fertile tetraploid, which results in very low genetic diversity of this important crop. Coffee's genetic resources are rapidly disappearing due to various threats, such as human population pressure, leading to land conversion to agriculture, deforestation, and land degradation; low coffee prices, leading to the abandonment of coffee trees in forests and gardens in favor of other, more profitable crops; and climate change, which is causing increased pest and disease infestations, increased droughts, and unpredictable rainfall patterns. All of these factors threaten livelihoods in many coffee-producing countries. Interests in cocoa and coffee development may differ in their understanding of sustainable cocoa and coffee, their interests and their actions in advancing sustainable cocoa. This article analyzes the sustainability of cocoa and coffee at a large scale and analyzes the extent to which sustainability standards, policies, and development projects address sustainability issues and contribute to ecosystem services. This analysis is based on a literature review. Producers in the three countries and share concerns about price volatility, weak farmer organization and dependence on a few buyers. Producers in Sulawesi and the Central Region are compensating for low yields of cocoa and coffee production by diversifying cocoa and coffee systems. Public and private development actors are concerned about the low volume of production. Research so far has focused on biodiversity loss, which differs depending on the age of a country's cocoa and coffee sector. Development policies and programs in all countries have focused on expanding the cocoa and coffee sectors and increasing productivity, despite the need for smallholders for economically viable farming systems and existing market structures that yield little bargaining power for farmers. Sustainability standards have been spread unevenly and have converged on compliance criteria over time, although they differed in focus initially. Recently added business criteria and the development of sustainability standards have the potential to address smallholder concerns. Keywords: Cocoa and Coffee Beans, Sustainability Standards, Sustainable coffee and cocoa production.